ANALYZING THE USE OF IN MEDIAS RES TECHNIQUE IN STUDENTS’ WRITING - Mulyaningsih, Tri (PENA KREATIF : JURNAL PENDIDIKAN, 2025)
This study investigates the technique of in medias res used by the sixth-semester students of English Education Study Program at the Teacher Training and Education Fakulty and the challenges they face in implementing it. In medias res is one of the narrative techniques that begin in the midst of the action. In medias res is often used to create a dynamic opening and engage the readers promptly. Despite the fact that it is common to find in medias res in narrative fiction, its application in the classroom is still unexplored. This study employed a mixed-method approach. A set of students-written short stories was analysed using the rubric to evaluate the effectiveness of in medias res implementation, coherence, creativity, and overall narrative structure. In addition, surveys and interview were conducted to gather data about their perception and experience. The finding reveals that while many students were able to apply the in medias res technique, they still encountered challenges in choosing the right moment in the storyline to begin, revealing backstory naturally, and maintaining reader engagement while ensuring clarity.